Health cadre empowerment to use herbal plants for therapy and health in Girirejo Village, Imogiri, Bantul - Hastuti, Janatin; Rahmawati, Neni Trilusiana; Setyowati, Erna Prawita (Journal of Community Empowerment for Health, 2025)
Introduction: The high rate of obesity and hypertension in the productive age group demands special attention from various parties for early detection and treatment, which can be accomplished by empowering village health cadres. This community service program is intended to increase knowledge and skills in the use of herbal plants for therapy and health among health cadres in Girirejo Village, Imogiri, Bantul.Methods: This study, done as part of a community service program in September 2023, included 42 health cadres (women aged 25-62 years) from Girirejo Village, Imogiri, Bantul, Yogyakarta. Participants learned about the therapeutic and physiological benefits of using herbal plants. The materials delivered included identifying various herbal materials, making herbal combinations, and employing therapeutic plants for health purposes. Pre- and post-tests were given before and after education. Training is provided through the practice of making herbal infusions. Statistical analysis uses the paired t-test. Results: The results revealed a significant difference (p<0.001) in the mean pre-test (64.50 ± 15.23) and post-test (80.75 ± 15.21). This suggests that this education can help health cadres learn more about knowledge and the utilization of herbal plants.Conclusion: The study concluded that this community service program might increase understanding and skills of the use of herbal plants for the health of Health Cadres in Girirejo Village. Participants indicated their satisfaction with the program's implementation. It is proposed that a new Community Service Strategic Plan, which includes Girirejo Village Health Cadres, be designed as a structured, innovative, and forward-thinking program plan to strengthen the empowerment of health cadres and the natural potential of local wisdom